2012
DOI: 10.1002/cncy.21242
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of atypical epithelial cells as a high‐risk cytologic feature for malignancy in pancreatic cysts

Abstract: BACKGROUND: Pancreatic cysts are aspirated to assess whether a cyst is mucinous on one hand and malignant on the other. The authors' retrospective data have indicated that high-grade atypical epithelial cells (AECs) identified on cytology are a high-risk feature and a better threshold than ''positive'' for detecting malignancy. The objective of the current study was to assess the accuracy of AECs in predicting malignancy in pancreatic cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…The lack of well-established criteria for the various grades of dysplasia in mucinous cysts has hampered a more standardized approach to classification. However, given the management algorithm for mucinous cysts which recommends a conservative approach for cysts at low risk for malignancy,[12] it is imperative that the pathologist relate on the cytology report that a neoplastic mucinous cyst has been detected by FNA (e.g., Neoplastic: Other) and to relate the presence or absence of cytologically high-grade appearing epithelium (e.g., high-grade epithelial atypia that represents at least high-grade dysplasia and possibly invasive carcinoma[1213] (see Category IV).…”
Section: Category Iii: Atypicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of well-established criteria for the various grades of dysplasia in mucinous cysts has hampered a more standardized approach to classification. However, given the management algorithm for mucinous cysts which recommends a conservative approach for cysts at low risk for malignancy,[12] it is imperative that the pathologist relate on the cytology report that a neoplastic mucinous cyst has been detected by FNA (e.g., Neoplastic: Other) and to relate the presence or absence of cytologically high-grade appearing epithelium (e.g., high-grade epithelial atypia that represents at least high-grade dysplasia and possibly invasive carcinoma[1213] (see Category IV).…”
Section: Category Iii: Atypicalmentioning
confidence: 99%
“…[12] Cells smaller than a 12 μ duodenal enterocyte showing an increased nuclear to cytoplasmic ratio, an abnormal chromatin pattern and background necrosis represent high-grade epithelial atypia placing the cyst at high-risk for malignancy. [213464748]…”
Section: Category Iv: Neoplasticmentioning
confidence: 99%
“…These hurdles make it difficult to reach a formal determination of 'positive' cytology. Cytopathologists from our institution have shown that lowering the threshold from 'positive' cytology to presence of high-grade atypical epithelial cells (which are quantitatively and qualitatively insufficient for a positive cytology interpretation), we can achieve an increase in the accuracy (80-85%) and in the number of cases of HGD and invasive carcinoma detected (12% more than when using 'positive' cytology) [57,58]. Lastly, the continuous progress in genomic technologies holds the promise of accurate diagnosis and risk stratification of pancreatic cysts using molecular analysis of cyst fluid.…”
Section: Cyst Fluid Analysis: Proteins Cytology and Molecular Charamentioning
confidence: 99%
“…In one study looking at the overall agreement between cytopathologists when applying a two‐tiered approach to grading mucinous cyst atypia (low or high‐grade), a poor performance was noted particularly in histologically confirmed low‐grade cysts, with many of the cytopathologists over‐interpreting the grade of atypia . In contrast, however, most studies have shown that the cytological grade of a mucinous cyst correlates well with histology, with high‐grade atypia being the only statistically significant predictor of malignancy . Grading the atypia of the cyst lining cells is of utmost importance, since low‐grade lesions are usually managed conservatively, and high‐grade lesions require prompt surgical intervention.…”
Section: Experience With the Use Of The Pb System Worldwidementioning
confidence: 99%
“…The incorporation of the PB System, as described in the present review, has also assisted its improvement. The use of ROSE has also shown to increase diagnostic yield, decreasing the number of nondiagnostic samples, time of the procedure, and complications . More recently, next‐generation “core‐type” needles have been used, producing larger tissue fragments.…”
Section: Future Perspectivesmentioning
confidence: 99%